2014
DOI: 10.5535/arm.2014.38.6.827
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factors Predicting Early Recovery of Pre-fracture Functional Mobility in Elderly Patients With Hip Fracture

Abstract: ObjectiveTo investigate the prognostic factors predicting the recovery of pre-fracture functional mobility, we evaluated this by the use of ambulatory assistive devices in short-term follow-up.MethodsFive hundred and fifty-three elderly patients who had undergone hip fracture operations from January 2006 to June 2013 were enrolled in this retrospective study. Clinical characteristics and predicted factors affecting functional recovery, such as the delay of rehabilitation after the operation, were reviewed. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 31 publications
5
34
0
5
Order By: Relevance
“…Type of fracture was found to be related to the postoperative ambulatory capacity, consistent with other studies [1720]. Our study showed a higher incidence of intertrochanteric and subtrochanteric fractures than that of femoral neck fracture.…”
Section: Discussionsupporting
confidence: 92%
“…Type of fracture was found to be related to the postoperative ambulatory capacity, consistent with other studies [1720]. Our study showed a higher incidence of intertrochanteric and subtrochanteric fractures than that of femoral neck fracture.…”
Section: Discussionsupporting
confidence: 92%
“…Several studies examined factors that affect functional outcome and mortality; such factors include age, preinjury walking ability, comorbidities, cognitive function, gender, the surgical modality, the fracture type, the duration from injury to operation, postoperative delirium, pressure ulcers, and nutritional status [3,11,[17][18][19][20]. These studies report that older age or walking disability prior to injury are risk factors for mortality and functional deterioration, meaning that a patient cannot be discharged home [11,17,18]. Age greater than 85 years is a risk factor for a less satisfactory functional outcome and a low chance of home discharge after hip fracture [8,11].…”
Section: Discussionmentioning
confidence: 99%
“…(2) This study was primarily aimed at evaluating the influence of anaesthesia on postoperative mobilisation. Considering weight bearing and walking after hip fracture surgery is hugely influenced by the pre-fracture mobility status of patients with hip fracture, the fracture type (extra or intra-capsular), and operative fixation (hemiarthroplasty, dynamic hip screw, or intramedullary nail) performed; 25 and are therefore, are more relevant as an outcome measure to evaluate the impact of surgical factors on postoperative mobilisation. (3) Although pain is considered as a limiting factor for postoperative rehabilitation following hip fracture surgery, 14 it is the dynamic pain (associated with mobilising patient out-of-bed) 13 which is more relevant to postoperative rehabilitation and is influenced by anaesthetic techniques.…”
Section: Exclusion Criteriamentioning
confidence: 99%